Percepire e comprendere - Costa, Vincenzo (Bollettino Filosofico, 2018)
Phenomenology has mostly focused on the concept of world rather than on that of psychological subject. In this paper, I highlight immanence as a mode of giveness of transcendence rather than a “private” content. The object is not a multiplicity of data of sensation and the appearance is the thing as determined from a certain point of view, namely, how could anyone see it in a particular spatial orientation. Therefore there is a constant dialectic between immanence and transcendence and the immanent aspects determine how transcendent things must be understood. As a result, being as consciousness and being as reality are constituted within the same transcendental movement and a full understanding of words only emerges when we know how to apply them both in relation to worldly contexts and in relation to our lived experience. This is the meaning of the idea according to which all reality ultimately exists by virtue of a sense-bestowal.